Empowering homes? Unravelling the connection between energy efficiency and well-being - Andrés Estévez; Miguel Angel Tovar Rea\~nos (The Economic and Social Research Institute (ESRI), 2024)
We study how residential energy efficiency impacts well-being. We propose an innovative framework to assess the effects of investments in energy efficiency through the lens of energy poverty experiences. Leveraging a novel micro-level dataset of Irish households' and buildings' characteristics, we find that improvements in energy efficiency lead to modest improvements in households capacity to afford adequate warmth. These effects are concentrated at the lower end of the energy efficiency and income distributions. Income emerges as the key determinant of energy poverty, while other household characteristics like home ownership also influence risk. Overall, the relationship between energy efficiency and energy affordability appears to be weak. Our results suggest that energy efficiency investments are unlikely to deliver the large welfare and environmental benefits widely expected from them, raising questions about their role in achieving a just energy transition.
Keywords: D74; L25; O15; O17; 330; Energy efficiency; energy poverty; well-being